MODAL SOSIAL DAN KEBERDAYAAN KELOMPOKTANI PADI DI KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Sendri Sendri; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims:1) to identify social capital rice farmersgroup in Rimba Melintang subdistric. 2) toidentify the empowerment level of rice farmersgroup in Rimba Melintang subdistric. 3) toidentify the correlation of social capital and the empowerment level of rice farmers group in Rimba Melintang subdistric. This research uses a survey method that consist of 63 farmers as respondents who were selected purposively. To identifythe social capital and empowerment in this research using a descriptive qualitative method. To identify the correlation of social capital and empowerment in this research using graph percentage method. The result showed that: 1) implementation of social capital for beginner class farmers group was low due to not all of elements of social capital were executed. For advanced and intermediate classes of farmers group, the implementation of social capital was high due to the all elements of social capital have been executed. 2) The empowerment for beginner class farmers group was low, while the empowerment for advanced and intermediate classes of farmers group was high. 3) The percentage of social capital for beginner class was 39.47% followed by empowerment 41.67%. The percentage of social capital for advanced class was 81.58% followed by empowerment 83.33%, while the percentage of social capital for intermediate class was 86.84% followed by empowerment 100%.Keywords:Social capital, Empowerment, Correlation, Farmers group